Description of Creep of The Lignostone in Biaxial Stress States - Czech, M. (Engineering Transactions, 1993)
The results of creep investigations of the beech-wood lignostone specimens cut along the grains are presented. In the two-dimensional stress state the shearing stress is kept constant while the tensile stress varies. The description of creep of the lignostone as a nonlinear and orthotropic material is proposed by means of the equations [...].This description has been found to be satisfactory.